Advancing interests through informal voice: a study of professional workers in Sri Lanka's knowledge outsourcing sector. (14th March 2017) - Fernando, Weerahannadige Dulini Anuvinda
Abstract : Drawing on a rhetorical approach, this article examines how early career professional workers challenge 'ideal worker expectations' through informal voice. Informal 'voice' is shown as a powerful way of advancing workers' interests, leading to incremental changes that improve their conditions of work. Striking are the power dynamics underpinning informal voice. Highlighting how ideal worker expectations are continuously legitimised and de‐legitimised as employees and their managers rhetorically engage with each other, ideal worker expectations are theorised as a process while illuminating a pluralistic, contextualised view of organisational culture shaped by the past, present and anticipated future.